Fatphobia, bullying and violence at school: a study in social representations with pre-teenagers - Cruz da Silva Souza, Valdelice (2022)
This article presents part of the results of a master's research regarding social representations and feelings of pre-adolescents about fatphobia, relating it to bullying, violence and school difficulties. It is a qualitative research that had Serge Moscovici's Theory of Social Representations was guiding axis and was developed in 3 (three) public schools in Sidrolândia - MS with 16 (sixteen) students from the 5th year of Elementary School, for through focus groups, one in each school. The data were transcribed and analyzed from the perspective of Bardin's content analysis. The results reveal that the body can be seen as a device of differences and intimidation due to its structure. For students, fatphobia is portrayed as bullying, which causes discomfort and discouragement from attending school due to abuse and violence, directly affecting their academic development. It was clear the feeling of pain and suffering for those who are outside the socially required standard. With this, the students internalize the negative representations about their own bodies and externalize their suffering in an aggressive way, causing violence to occur daily at school, which makes it an unsafe and totally unprepared place.